Less basal thyrotropin levels predict antidepressant response in patients with major depression - R. Navinés; G. Oriolo; M. Mora; M. Cavero; E. Gómez-Gil; R. Martin-Santos (European Psychiatry, 2022)
Introduction The close association among thyroid metabolism, mood disorders and behavior has long been known. The role of basal thyroid axis in antidepressant treatment response is less known.